A Brief Report on a Reduced Preference for Passive-Avoidant Leadership After a Restless Night - Nordmo, Morten; Olsen, Olav Kjellevold; Rosseland, Ragna; Blågestad, Tone Fidje; Pallesen, Ståle (Frontiers in Psychology, 2018)
The purpose of this study is to investigate the effect of fragmented sleep on followers’ leadership preferences. In a counterbalanced experimental study involving 39 followers, changes in leadership preferences were recorded after one night of fragmented sleep (awakened every 80 minutes during the night), compared to a rested condition with the conditions separated by seven nights. The results showed that the participants rated passive-avoidant leadership less ideal, after one night of fragmented sleep. No differences regarding preference for transactional or transformational leadership occurred. Thus, negative perceptions of leaders may partly stem from reduced sleep patterns. However, further studies are needed to confirm this finding.